Validity of the Africa-wide Lang Factor of 2.63 for Estimating Small Biogas Plant Installation Costs in Uganda - Ndyabawe, Kenneth; Kisaalita, William S. (International Journal of Agricultural and Biological Engineering, 2014)
There is an increasing interest in popularizing small biogas plants to meet the bulk of domestic energy needs in Africa for cooking, lighting, and other activities such as cooling or refrigeration. As stakeholders (policy makers, donors, credit providers, sector experts, and product development professionals) contemplate programs, one of the key questions to which a reliable answer is needed is biogas plant installation cost that may vary from region to region. An Africa-wide materials
Keywords: biogas, fixed capital investment, Lang factor, Uganda, renewable energy